A Review of NEPA, a Novel Fixed Antiemetic Combination with the Potential for Enhancing Guideline Adherence and Improving Control of Chemotherapy-Induced Nausea and Vomiting. (3rd September 2015) - Hesketh, Paul J.; Aapro, Matti; Jordan, Karin; Schwartzberg, Lee; Bosnjak, Snezana; Rugo, Hope
Abstract : Combination antiemetic regimens targeting multiple molecular pathways associated with emesis have become the standard of care for prevention of chemotherapy-induced nausea and vomiting (CINV) related to highly and moderately emetogenic chemotherapies. Antiemetic consensus guidelines from several professional societies are widely available and updated regularly as new data emerges. Unfortunately, despite substantial research supporting the notion that guideline conformity improves CINV control, adherence to antiemetic guidelines is unsatisfactory. While studies are needed to identify specific barriers to guideline use and explore measures to enhance adherence, a novel approach has been taken to improve clinician adherence and patient compliance, with the development of a new combination antiemetic. NEPA is an oral fixed combination of a new highly selective NK1 receptor antagonist (RA), netupitant, and the pharmacologically and clinically distinct 5-HT3 RA, palonosetron. This convenient antiemetic combination offers guideline-consistent prophylaxis by targeting two critical pathways associated with CINV in a single oral dose administered only once per cycle. This paper will review and discuss the NEPA data in the context of how this first combination antiemetic may overcome some of the barriers interfering with adherence to antiemetic guidelines, enhance patient compliance, and offer a possible advance in the prevention of CINV for patients.